Facile Synthesis of Pd@PtM (M = Rh, Ni, Pd, Cu) Multimetallic Nanorings as Efficient Catalysts for Ethanol Oxidation Reaction - Wu, Xingqiao; Li, Xiao; Yan, Yucong; Luo, Sai; Huang, Jingbo; Li, Junjie; Yang, Deren; Zhang, Hui (Frontiers in Chemistry, 2021)
Pt-based multimetallic nanorings with a hollow structure are attractive as advanced catalysts due to their fantastic structure feature. However, the general method for the synthesis of such unique nanostructures is still lack. Here we report the synthesis of Pd@PtM (M = Rh, Ni, Pd, Cu) multimetallic nanorings by selective epitaxial growth of Pt alloyed shells on the periphery of Pd nanoplates in combination with oxidative etching of partial Pd in the interior. In situ generation of CO and benzoic acid arising from interfacial catalytic reactions between Pd nanoplates and benzaldehyde are critical to achieve high-quality Pt-based multimetallic nanorings. Specifically, the in-situ generated CO promotes the formation of Pt alloyed shells and their epitaxial growth on Pd nanoplates. In addition, the as-formed benzoic acid and residual oxygen are responsible for selective oxidative etching of partial Pd in the interior. When evaluated as electrocatalysts, the Pd@PtRh nanorings exhibit remarkably enhanced activity and stability for ethanol oxidation reaction (EOR) compared to the Pd@PtRh nanoplates and commercial Pt/C due to their hollow nanostructures.